Global human influence maps reveal clear opportunities in conserving Earth's remaining intact terrestrial ecosystems. (5th June 2020) - Riggio, Jason; Baillie, Jonathan E. M.; Brumby, Steven; Ellis, Erle; Kennedy, Christina M.; Oakleaf, James R.; Tait, Alex; Tepe, Therese; Theobald, David M.; Venter, Oscar; Watson, James E. M.; Jacobson, Andrew P.
Abstract: Leading up to the Convention on Biological Diversity Conference of the Parties 15, there is momentum around setting bold conservation targets. Yet, it remains unclear how much of Earth's land area remains without significant human influence and where this land is located. We compare four recent global maps of human influences across Earth's land, Anthromes, Global Human Modification, Human Footprint and Low Impact Areas, to answer these questions. Despite using various methodologies and data, these different spatial assessments independently estimate similar percentages of the Earth's terrestrial surface as having very low (20%–34%) and low (48%–56%) human influence. Three out of four spatial assessments agree on 46% of the non‐permanent ice‐ or snow‐covered land as having low human influence. However, much of the very low and low influence portions of the planet are comprised of cold (e.g., boreal forests, montane grasslands and tundra) or arid (e.g., deserts) landscapes. Only four biomes (boreal forests, deserts, temperate coniferous forests and tundra) have a majority of datasets agreeing that at least half of their area has very low human influence. More concerning, <1% of temperate grasslands, tropical coniferous forests and tropical dry forests have very low human influence across most datasets, and tropical grasslands, mangroves and montane grasslands also have <1% of land identified as very low influence across all datasets. These findings suggest that about half of Earth's terrestrial surface has relatively low human influence and offers opportunities for proactive conservation actions to retain the last intact ecosystems on the planet. However, though the relative abundance of ecosystem areas with low human influence varies widely by biome, conserving these last intact areas should be a high priority before they are completely lost. Abstract : Leading up to the Convention on Biological Diversity Conference of the Parties 15, there is momentum around setting bold conservation targets. Yet it remains unclear how much of Earth's land area remains without significant human influence. We compare four recent global maps of human influences (Anthromes, Global Human Modification, Human Footprint, and Low Impact Areas) and find that about half of Earth's terrestrial surface has relatively low human influence. These findings offer opportunities for proactive conservation actions to retain the last intact ecosystems on the planet, although the relative abundance of ecosystem areas with low human influence varies widely by biome.